2009
DOI: 10.1177/1352458509107008
|View full text |Cite|
|
Sign up to set email alerts
|

25-Hydroxyvitamin D in cerebrospinal fluid during relapse and remission of multiple sclerosis

Abstract: Hypovitaminosis D may play a role in multiple sclerosis (MS), but little is known about intrathecal vitamin D. 25-Hydroxyvitamin D was measured in cerebrospinal fluid and sera from 36 patients with relapsing-remitting MS, 20 patients with other inflammatory neurological diseases and 18 patients with non-inflammatory neurological diseases with liquid chromatography-mass spectrometry. There were no significant differences in cerebrospinal fluid concentrations of 25-hydroxyvitamin D, but the cerebrospinal fluid:s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 15 publications
2
46
1
3
Order By: Relevance
“…Jugdeep et al [36] found no significant changes in the SF-36 scores of subjects who received a single intramuscular injection of 600 000 IU ergocalciferol, whereas a different study demonstrated an improvement in seasonal affective disorder as a result of vitamin D supplementation [37] . In our study, there were significant decreases in PF, VT, SF, and MF scores on the SF-36 at the 12- [38] . In situ, vitamin D exerts its effects via vitamin D receptors, which are nuclear hormone receptors that are expressed in cerebral neurons.…”
Section: Discussionsupporting
confidence: 54%
“…Jugdeep et al [36] found no significant changes in the SF-36 scores of subjects who received a single intramuscular injection of 600 000 IU ergocalciferol, whereas a different study demonstrated an improvement in seasonal affective disorder as a result of vitamin D supplementation [37] . In our study, there were significant decreases in PF, VT, SF, and MF scores on the SF-36 at the 12- [38] . In situ, vitamin D exerts its effects via vitamin D receptors, which are nuclear hormone receptors that are expressed in cerebral neurons.…”
Section: Discussionsupporting
confidence: 54%
“…A Norwegian study failed to detect an inverse correlation between serum 25(OH)D levels and MS disease activity [90]. This study was the first to quantify and compare the 25(OH)D and 1,25(OH) 2 …”
Section: Vitamin D In Relapsingeremitting Multiple Sclerosismentioning
confidence: 97%
“…However, they could not find any significant difference between the levels of the biologically active vitamin D metabolite, 1,25(OH)D in MS patients and controls as well as no association with relapse or gadolinium-enhanced lesions was determined [76].…”
Section: Vitamin Dmentioning
confidence: 99%